Influence of Nano Silica on the Geotechnical Properties of Clayey Soil Stabilized with Lime - Iswarya, R.; Satheeskumar, V. (Asian Journal of Engineering and Applied Technology, 2018)
The soil must be able to withstand the load and transfer it to ground within the range of allowable deformations, for which it must possess good physical and geotechnical properties. The conventional method of stabilization such as removal and replacement of ill – suited soils incur higher cost and is time consuming. A new method of stabilization, designated as chemical stabilization can be adopted. This method initiate chemical reactions such as cation exchange, pozzolanic activity etc., which consequently enhance the geotechnical properties of soil. In this study, the mechanical behavior of soil is improved by addition of nanoparticles i.e., nano silica along with cementitious material, lime. Considering economic issues of nano silica usage and results of this research in soil stabilization projects, in this study 0, 1, 3 and 5 % weight of nano silica is used as well as 0, 2 and 4 % weight of lime is used. The effect of these replacements is studied by Atterberg limits test, compaction test and unconfined compressive strength (UCS) test. The effect of curing time on samples at 3, 7 and 28 days of age has also been investigated. The optimum percentage replacement of nano silica in lime stabilized soil is determined. The microstructure of the stabilized soil is studied by Scanning electron microscopy (SEM) test. Thus the results proved that there is a significant improvement in the plasticity, compaction and strength properties with slight addition of nano silica in clayey soil mixed with lime.